Categorizing errors in high‐reliability organizations: adaptive range and adaptive capacity in incident response - Kutsch, Elmar; Siala, Haytham; Cantarelli, Chantal C.; Djabbarov, Ibrat (Wiley, 2025)
This study examines how actors in a high‐reliability organization categorize errors as near‐misses or accidents through the lens of adaptive capacity and adaptive range. We studied a large defense entity with operations critical to national security to understand how organization members categorized errors during incidents. Using the repertory grid method to interview informants, we identify key dualities that actors navigate between anticipatory and retrospective responses to errors. These dualities collectively reflect the organization's adaptive capacity and adaptive range when balancing anticipatory and retrospective responses. Our analysis of error categorization through this lens provides new insights into how high‐reliability organizations manage incidents to maintain reliability and offers practical implications for enhancing organizational resilience in high‐risk settings.
Keywords: 3505 Human Resources and Industrial Relations; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; accidents; errors; high‐reliability organizations; organizational response; repertory grid; Strategic, Defence & Security Studies